Las primeras aventuras de Aura - Valdés, Gabriel Ángel (Edición Digital, 2014)
This first novel tells the story of Aura, a twelve year old receives the unexpected news of his mother Celeste on a vacation trip to a magical world called Admar. Aura, addicted to reading and fantasy books, this trip looks like your dream come true. Dream that is frustrated in the moment of entering that world, because a war breaks out and makes those beautiful holiday in a constant battle against The Masters of Death, who are blinded by the power of Mana energy that makes up all things that make Cosmic Loom.